Receptor expression and responsiveness of human peripheral blood mononuclear cells to a human cytomegalovirus encoded CC chemokine - Zheng,Qi (2015)
Human cytomegalovirus is a ubiquitous pathogen that infects the majority of the world's population. After long period of time co-evolving with human being, this pathogen has developed several strategies to evade host immune surveillance. One of the major trick is encoding homologous to those of the host organism or stealing host cellular genes that have signiﬁcant functions in immune system. To date, we have found several viral immune analogous which include G protein coupled receptor, class I major histocompatibility complex and chemokine. Chemokine is a small group of molecules which is deﬁned by the presence of four cysteines in highly conserved region. The four kinds of chemokines (C, CC, CXC, and CX3C) are classiﬁed based on the arrangement of 1 or 2 N-terminal cysteine residues. UL128 protein is one of the analogous that encoded by human cytomegalovirus that has similar amino acid sequences to the human CC chemokine. It has been proved to be one of the essential particles that involved in human cytomegalovirus entry into epithelial/endothelial cells as well as macrophages. It is also the target of potent neutralizing antibodies in human cytomegalovirus-seropositive individuals. We had demonstrated the chemotactic trait of UL128 protein in our previous study. Recombinant UL128 in vitrohas the ability to attract monocytes to the infection region and enhances peripheral blood mononuclear cell proliferation by activating the MAPK/ERK signaling pathway. However, the way that this viral encoded chemokine interacting with peripheral blood mononuclear cells and the detailed mechanism that involving the virus entry into host cells keeps unknown. Here we performed in vitroinvestigation into the effects of UL128 protein on peripheral blood mononuclear cell's activation and receptor binding, which may help us further understand the immunomodulatory function of UL128 protein as well as human cytomegalovirus diffusion mechanism.